PROBLEMA PENDIDIKAN AGAMA HINDU PADA KELUARGA DENGAN LATAR BELAKANG PERKAWINAN LINTAS AGAMA - I Made Nuhari Anta (STAH Dharma Sentana Sulawesi Tengah, 2020)
Problem formulation: (1) Why does Hindu religious education in families with interfaith marital backgrounds have problems? This study aims: to obtain an overview of education in Hindu families who marry interfaith. To dissect the problem in this study using qualitative methods with the Phenomenological Theory, Theory of Constructionvism, and Beavioristic Theory. Data collection techniques in this study were observation, interviews, document studies, documentation and literature. Data analysis techniques in this study refer to the analytical steps proposed by Kaelan consisting of data reduction, data classification, and data display, providing interpretation and giving conclusions. The results showed that the problem of Hindu religious education in families with interfaith marital backgrounds consisted of: (a) Problems of Ceremonies and Upakara; (b) Difference between the concept of God and the previous religion; (c) Problems in Using Local Languages ​​(Balinese); (d) Lack of Attention from Husband to Teach Hinduism; (e) Economic and Traditional Issues